CONCERNING BRONZE AGE FUNERARY FINDS FROM MEDIAŞ - Cristian Ioan POPA (Journal of Ancient History and Archaeology)
The paper discusses certain funerary finds, especially some possible ones, belonging to the Bronze Age, from the Mediaş-“Hăşmaş” site. Besides a Wietenberg cremation grave, there are arguments for including other finds among those with a Wietenberg funerary character, including a vessel conserved in the Mediaş museum, which outlines a group of graves in the respective site. Another discovery, kept in the same museum, may belong to a funerary discovery, namely a quadrilobed vessel with a perforated bottom, which documents burials during the Late Bronze, at the level of the Gligoreşti group, or the Noua culture. As we are talking about ancient finds, some without a precise context, certain information is missing, but those that could be recovered indicate some burials during the Middle and Late Bronze.